INVALIDITY OF CIVIL LAW TRANSACTIONS RESULTING FROM CORRUPTION CASES - Rakhmonaliyev Zikrullo Iqboljon ogli (Bright Mind Publishing, 2025)
This paper examines the legal mechanisms for invalidating civil law transactions arising from corruption, focusing on recent legislative developments and their practical implementation. The study analyzes the correlation between anti-corruption laws and civil code provisions concerning void and voidable transactions, with particular emphasis on public procurement, licensing, and property transactions. Statistical data from 2022-2024 reveals a significant increase in civil cases challenging the validity of corrupt transactions, with courts invalidating approximately 63% of such contested agreements. The research demonstrates that while legislative frameworks have been strengthened, procedural obstacles and enforcement challenges persist. The paper concludes that effective invalidation of corrupt transactions requires multi-faceted approaches combining administrative, criminal, and civil remedies, with recommendations for legislative reform to enhance the efficiency of civil law mechanisms in combating corruption.
Keywords: Corruption, civil law transactions, invalidity, void transactions, voidable transactions, anti-corruption legislation, public procurement, legal remedies, civil litigation.